Presenilin 1 and APP gene mutations in early‐onset AD families from a southeast region of China: Genetics/genetic factors of Alzheimer's disease. (7th December 2020) - Peng, Guoping
Abstract: Background: Early‐onset familial Alzheimer's disease (EOFAD) has been reported to be associated with presenilin 1 (PSEN1), presenilin 2 (PSEN2), and amyloid precursor protein (APP) genes. The spectrum of mutations in Chinese patients with EOFAD was rarely investigated. Thus, this study intends to investigate the spectrum of mutations in patients with EOFAD in Chinese population. Method: We performed a whole‐exome sequencing and described relevant clinical features in a total of 67 patients from 3 families with EOFAD. Result: A splice mutation (p.S290C) in PSEN1 and a missense mutation (p.V717I) in APP were identified. Conclusion: The variant p. S290C (c.869‐2>G) in PSEN1 in Chinese EOAD family revealed different clinical phenotype when compared with that of European.